Optimasi Jalan Pahat Dan Analisis Biaya Produksi Proses Pemesinan CNC Lathe Pembuatan Piston Master Cylinder Rem Sepeda Motor Yamaha Menggunakan CAM - Nico Atmadio; Anita Susilawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Tool path optimation on CNC lathe machining can set up every movement of tools move optimally to minimize processing time of a workpiece. This research purpose is simulation of tool path the CNC lathe machining for the manufacture of piston master cylinder brake of Yamaha Motorcycle by using CAD/CAM software. First design was made geometry of piston master cylinder using Computer Aided Design (CAD). Tool path was designed into 3 variations of scheme with absolute and increment of programming system using Mastercam v9. Then it was simulated to get the most optimum processing time. Simulation result was obtained longitudinal scheme time for absolute coordinate system 14 minutes 45 seconds and increment coordinate system 14 minutes 5 seconds, surface to parallel scheme for absolute coordinate system 14 minutes 30 seconds and increment coordinate system 13 minutes 48 seconds, diametrical scheme for absolute coordinate system 17 minutes 39 seconds and increment coordinate system 17 minutes 12 Seconds. The optimal processing time for making the piston master cylinder brake of Yamaha Motorcycle used the toll path of surface to parallel increment coordinate system with production cost Rp. 6.912,81,-/pcs.Keywords : Piston master cylinder, Tool Path, Absolut, Inkremen.